2021
DOI: 10.3390/cancers13143378
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis of Circulating Cell-Free DNA’s Role in the Prognosis of Pancreatic Cancer

Abstract: Introduction: The analysis of cell-free DNA (cfDNA) for genetic abnormalities is a promising new approach for the diagnosis and prognosis of pancreatic cancer patients. Insights into the molecular characteristics of pancreatic cancer may provide valuable information, leading to its earlier detection and the development of targeted therapies. Material and Methods: We conducted a systematic review and a meta-analysis of studies that reported cfDNA in pancreatic ductal adenocarcinoma (PDAC). The studies were cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 85 publications
1
7
0
Order By: Relevance
“…The prognostic value of ctDNA has been evaluated in a recent meta-analysis of 48 studies of over 3000 patients with different stages of PC. This study found that the detection of KRAS mutations via ctDNA has a negative impact on OS and PFS in PC (HR = 2.42; 95% CI = 1.95 - 2.99 and HR = 2.46; 95% CI = 2.01 - 3.00, respectively) ( 94 ). In localized PC, detection of ctDNA preoperatively is associated with poorer RFS (HR = 4.1; P = 0.002) and OS (HR = 4.0; P = 0.003) ( 95 ).…”
Section: Pancreatico-biliary Cancermentioning
confidence: 93%
See 1 more Smart Citation
“…The prognostic value of ctDNA has been evaluated in a recent meta-analysis of 48 studies of over 3000 patients with different stages of PC. This study found that the detection of KRAS mutations via ctDNA has a negative impact on OS and PFS in PC (HR = 2.42; 95% CI = 1.95 - 2.99 and HR = 2.46; 95% CI = 2.01 - 3.00, respectively) ( 94 ). In localized PC, detection of ctDNA preoperatively is associated with poorer RFS (HR = 4.1; P = 0.002) and OS (HR = 4.0; P = 0.003) ( 95 ).…”
Section: Pancreatico-biliary Cancermentioning
confidence: 93%
“…Collectively, several studies have shown that ctDNA increase tends to precede clinical progression as determined by imaging and serum Ca19.9 level by a few months ( 100 102 ). In a meta-analysis of studies on patients with detectable KRAS before treatment, conversion to undetectable KRAS after treatment is associated with better prognosis ( 94 ). ctDNA has also been used to track other cancer-specific mutations such as TP53 , APC , ATM , FBXW7 , SMAD4 , CDKN2A and other variants ( 101 , 103 ).…”
Section: Pancreatico-biliary Cancermentioning
confidence: 99%
“…KRAS mutations are the most common target used for PDAC detection. Many studies have reviewed the available data in the literature and shown this [ 165 , 182 , 183 , 184 , 185 ]. KRAS mutations are rarely found in clones during age-associated clonal hematopoiesis, such as in DNMT3A, TET2, JAK2, ASXL1, TP53 , GNAS, PPM1D, BCORL1, and SF3B1.…”
Section: Circulating Cell-free Tumoral Dna (Ctdna)mentioning
confidence: 99%
“…The detection of mut- KRAS in aPDAs indicates poorer outcomes, as demonstrated by multiple studies [ 64 , 67 , 73 , 74 , 76 , 80 , 82 ]. A recent meta-analysis of 48 studies examined the prognostic role of mut- KRAS detection in cfDNA to provide a more comprehensive summary [ 83 ]. The study examined 3524 patients across all stages of the disease, before and after treatment (both surgical and pharmacologic).…”
Section: Prognostic Value Of Cfdna In Pdamentioning
confidence: 99%